Metal-Free Hydroamination of Alkynes: A Mild and Concise Synthesis of Thiazolo[3,2-a]indoles and their Cytotoxic Activity - Short, Spencer; Rhodes, Steven; Bhave, Vishakha S.; Hojo, Ryoga; Jha, Mukund (Synthesis, 2019)
A metal-free, mild and efficient method for the synthesis of thiazolo[3,2-a]indoles has been developed starting from indoline-2-thiones. The reaction methodology involves first the formation of thermally labile 2-(prop-2-ynylthio)-1H-indole intermediates, which undergo base-mediated intramolecular hydroamination to produce the title compounds in excellent yields.
Keywords: indole-fused heterocycles; thiazolo[3,2-a]indoles; metal-free hydroamination; indoline-2-thiones; intramolecular cyclization